20-80% Water-In-Diesel Emulsion Fuel Formulations and Stability Study for Duration of Two - Issaka, Souleyman A.; Nour, A. H.; R. M., Yunus (IJAR, 2015)
New surfactant formulations were prepared at FKKSA Lab at University Malaysia Pahang; the formulation consists of synthesized polyol based non-ionic surfactants combined with different concentrations of commercial stabilizers and co surfactants. Six different compositions denoted as Samples (A, B, C, D, E, F) were tested on 20-80% water-in-diesel emulsion fuel samples for duration of fortnights. Results showed that emulsions prepared with formulations C, D, E and F were very stable and showed no water separation for two weeks. Followed by B, which started separation after 13 days and lost 15% of the water, while sample A, which appeared to be the least stable of all, lost 15% of oil in the first day. From these data one can conclude that the samples (C, D, E and F) surfactant formulation could be used as tailored stabilizers for synthesizing diesel based emulsion fuels.